Citologia do lavado broncoalveolar de eqüinos da polícia militar do distrito federal - Costa, Nathalia dos Santos [UNESP]; Macoris, Delphim da Graça [UNESP] (My University, 2007)
The objective of this study was evaluate the airways' cells types from horses of the military police of Federal District. It was used 24 horses, divided into 2 groups of 12: group I - animals in policy activity and group II - animals out of policy activity. At the inspection, physical exam and blood exam, the results agreed with no present clinical pathologies. It was infused 240mL of saline solution in the bronchoalveolar wash. In the bronchoalveolar wash, the group I registered 25.25±7.3 squamous cells, 20.2±5.5 epithelial cells, 22.2±6.23 macrophages and 2.02±5.77 erythrocytes, and in the group II, it was observed 31.0±9.47 squamous cells, 19.0±5.20 epithelial cells, 43.0±13.88 macrophages, 4.0±1.52 eosinophile and 3.0±1.0 erythrocytes. Verifying the occurrence of side effects after the experiment, there was no problem from the used technique.
Brochoalveolar wash citology from horses of the military police in the federal district
Keywords: Bronchoalveolar; Citology; Equine; Wash; Animalia; Equidae